Cholesterol homeostasis: Researching a dialogue between the brain and peripheral tissues. (January 2021) - Gliozzi, Micaela; Musolino, Vincenzo; Bosco, Francesca; Scicchitano, Miriam; Scarano, Federica; Nucera, Saverio; Zito, Maria Caterina; Ruga, Stefano; Carresi, Cristina; Macrì, Roberta; Guarnieri, Lorenza; Maiuolo, Jessica; et al.
Graphical abstract: Highlights: Peripheral and CNS cholesterol metabolism are separated by the blood brain barrier (BBB) and are regulated independently. Cholesterol homeostasis dysfunction leads to metabolic, cardiovascular and neurological diseases that can be interconnected. Lipoproteins, miRNAs and oxysterols are involved in the cross talk between central and peripheral cholesterol metabolism. The modulation of cholesterol mediators suggests new perspectives in the management of cholesterol-related diseases. Abstract: Cholesterol homeostasis is a highly regulated process in human body because of its several functions underlying the biology of cell membranes, the synthesis of all steroid hormones and bile acids and the need of trafficking lipids destined to cell metabolism. In particular, it has been recognized that peripheral and central nervous system cholesterol metabolism are separated by the blood brain barrier and are regulated independently; indeed, peripherally, it depends on the balance between dietary intake and hepatic synthesis on one hand and its degradation on the other, whereas in central nervous system it is synthetized de novo to ensure brain physiology. In view of this complex metabolism and its relevant functions in mammalian, impaired levels of cholesterol can induce severe cellular dysfunction leading to metabolic, cardiovascular and neurodegenerative diseases. The aim of this review is to clarify the role of cholesterol homeostasis in health and disease highlighting new intriguing aspects of the cross talk between its central and peripheral metabolism.